Unlocking hidden sources of resistance to ascochyta blight in moderately resistant chickpea genotypes - Crociara, Clara Sonia; Valetti, Lucio; Castro, Patricia; Millán, Teresa; Iglesias, Juliana; Pastor, Silvina Estela (Springer, 2025)
Ascochyta blight, caused by Ascochyta rabiei, is a major threat to global chickpea (Cicer arietinum L.) production, significantly reducing yield under favorable conditions. This study aimed to characterize the resistance responses of nine chickpea genotypes, previously classified as moderately resistant, by subjecting them to enhanced disease pressure. Phenotypic evaluation, including the area under the disease progress curve (AUDPC) and severity scoring was carried out. To investigate the potential genetic basis of the observed resistance response, we analyzed molecular markers previously reported as linked to quantitative trait loci (QTLs) for A. rabiei resistance. The approach focused on testing whether these established markers could distinguish genotypes following the same patterns observed in their phenotypic responses under increased pathogen pressure. The results revealed significant variability among the MR genotypes, with three genotypes FLIP06-86C, FLIP07-35C, and FLIP03-100C outperforming the resistant control. The results from hierarchical clustering (UPGMA), principal component analysis (PCA), and principal coordinate analysis (PCoA) highlighted genetic substructures consistent with observed phenotypic behaviors. However, unexpected marker-phenotype associations were detected, questioning the utility of specific markers such as SCY17 and CaETR4 in marker-assisted selection. These findings underline the complexity of polygenic resistance to A. rabiei and emphasize the importance of integrating phenotypic screening with genetic analyses to improve the reliability of chickpea breeding programs. This work also contributes to identifying superior MR genotypes, providing valuable resources for the development of resistant cultivars.